Pi2 pulsation simultaneously observed in the E and F region ionosphere with the SuperDARN Hokkaido radar. Issue 5 (14th May 2014) - Teramoto, M.; Nishitani, N.; Pilipenko, V.; Ogawa, T.; Shiokawa, K.; Nagatsuma, T.; Yoshikawa, A.; Baishev, D.; Murata, K. T.
Abstract We investigated Pi2 pulsations in the nightside ionosphere that began at 14:15 UT (2315 LT) on 11 July 2010, and they were observed with high‐temporal (8 s) resolution by beam 4 of the Super Dual Auroral Radar Network (SuperDARN) Hokkaido radar. These pulsations were simultaneously observed in both the ground/sea scatter echoes reflected from the F region height and in ionospheric echoes from field‐aligned irregularities in the sporadic Es region. They had the same period of 110 s and approximately no phase lag. From the radar observations and the International Geomagnetic Reference Field model, the amplitude of the eastward (EEW) component of the electric field of the Pi2 pulsations in the ionosphere was estimated 8.0 mV/m in the F region and 2.0 mV/m in the E region. Corresponding Pi2 pulsations appeared dominantly in the horizontal northward magnetic field component (H) at nearby ground stations, Moshiri (MSR), St. Paratunka (PTK), and Stecolny (STC), with amplitudes ranging from 6 nT (MSR) to 10 nT (STC). At the dominant frequency of 8.8 mHz, the coherences between H and EEW were high (>0.9), the cross phases of EEW relative to H were −56° and −45°, and the amplitude ratios were 2.7 × 105 m/s and 8.4 × 105 m/s, in the E and F regions, respectively. Based on a comparison of these results with theoretical predictions, we suggest that the concept of a pure cavity mode is not sufficient to explain the combined observations for midlatitude Pi2 waves and that the contribution of an Alfvén waves must be taken in account.